The neonatal transfer process through the lens of neonatologists at public hospitals in South Africa - Pradeep Ashokcoomar; Raisuyah Bhagwan (AOSIS, 2022)
Background: Neonatal care is provided by various levels of healthcare facilities in South Africa. Intensive care for neonates is only provided at the higher levels, hence the need for transfers from lower-level to higher-level facilities (e.g. primary hospitals to tertiary hospitals) or across levels of facilities, particularly when life-threatening situations arise (e.g. cardiac deterioration, respiratory deterioration and desaturation). Aim: The aim of the study was to explore neonatologists' views regarding the neonatal transfer process and to describe the preparedness of advanced life support (ALS) paramedics to undertake such transfers. Setting: The setting consisted of neonatologists from three provinces i.e. KwaZulu-Natal, Gauteng and Western cape. Method: A qualitative descriptive design was utilised in this study. Semistructured interviews were conducted on the public health hospitals in three provinces (N = 9; n = 3) with neonatologists (N = 7; n = 7) who were involved in the transfers of critically ill neonates. The process of thematic analysis was used. Results: The themes that emerged in this study were: an awareness of local contextual realities related to neonatal transfers, challenges evident within the context of neonatal transfers, decision-making around the transfer of ill neonates, ALS paramedic preparedness for transfers and good clinical governance Conclusion: The study found that there was a need to be aware of local contextual realities confronting neonatal transfers, a need for greater preparedness for paramedics to undertake these transfers, a need for a sound referral processes and a need for coordinated transfer effort between paramedics, hospital staff and transport team members for the successful transfer of critically ill neonates. Contribution: The findings highlight the challenges confronting the neonatal transfer process in South Africa through the lens of neonatologist at public hospitals. Hence, the study reinforces the preparedness and coordination of the transfer process, along with more efficient communication between paramedics, hospital staff and the transfer team.